Structure–properties relationships in dental adhesives: Effect of initiator, matrix monomer structure, and nano-filler incorporation. Issue 9 (September 2018) - Azad, Elham; Atai, Mohammad; Zandi, Mojgan; Shokrollahi, Parvin; Solhi, Laleh
Abstract: Objectives: This is a confirmatory study to evaluate the effect of photoinitiator type and concentration, matrix monomer chemical structure, and nanoparticle incorporation on the physical and mechanical properties of an experimental dentin bonding agent. Materials and methods: Different concentrations of camphorquinone-amine (CQ-A) system, butanedione (BD), and phenylpropanedione (PPD), as photoinitiator, BTDMA, as a comonomer containing carboxylic acid groups, and silica nanoparticles as reinforcing inorganic filler were incorporated into a methacrylate base experimental dental adhesive. The effect of these ingredients, as independent variables, on the shrinkage kinetics, flexural strength and modulus, and microshear bond strength of the adhesives were then investigated. The results were analyzed using one-way ANOVA and Tukey's post-hoc test at the significance level of 0.05. Results: The results indicate that the efficiency of CQ-A initiator system is diminished in the presence of the acidic monomer BTDMA while the photopolymerization is efficiently progressed with BD as initiator. PPD shows the lowest efficiency in the photopolymerization of the adhesives. BTDMA as a monomer with the capability of interaction with tooth structure provides adhesive with improved microshear bond strength to dentin. Incorporation of silica nanoparticles at low concentrations enhances the flexural and microshear strength of the dentin bonding agent. Significance: Understanding the structure–property relationship in dental adhesives may help the material selection in clinical dentistry. The study elucidates the relationship between monomer structure, initiator type, and nanofiller and physical and mechanical properties in dental adhesives.